Coupling of surface pCO2 and dissolved oxygen in the northern South China Sea: impacts of contrasting coastal processes - M. Dai; W.-J. Cai; W. D. Zhai (Biogeosciences, 2009)
We examined the relationship between CO2 partial pressure (pCO2) and dissolved oxygen (DO) based on a cruise conducted in July 2004 to the northern South China Sea (111°–118° E 18°–23° N), spanning from estuarine plume, coastal upwelling and deep basin areas. Distinct relationships between pCO2 and DO saturation were identified in different regimes. In coastal upwelling areas and the Pearl River estuary, biological drawdown of pCO2 and production of O2 were simultaneously observed. The two properties were coupled with each other primarily via photosynthesis and respiration. The stoichiometric relationship of the two properties however, was quite different in these two environments due to different values of the Revelle factor. In the offshore areas, apart from the estuary and upwelling, the dynamics of pCO2 and DO were mainly influenced by air-sea exchange during water mixing. Given the fact that air-sea re-equilibration of O2 is much faster than that of CO2, the observed pCO2-DO relationship deviated from that of the theoretical prediction based on the Redfield relationship in the offshore areas. Although this study is subject to the limited temporal and spatial coverage of sampling, we have demonstrated a simple procedure to evaluate the community metabolic status based on a combination of high-resolution surface pCO2 and DO measurements, which may have applicability in many coastal systems with a large gradient of changes in their physical and biogeochemical conditions.